Antifungal effect of Sticophus hermanii and Holothuria atra extract and its cytotoxicity on gingiva-derived mesenchymal stem cell - Kristanti Parisihni; Syamsulina Revianti (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2013)
Background: Sea cucumber had been acknowledged to have some medical properties Sticophus hermanii and Holothuria atra are species of sea cucumber which has been known to have antifungal properties thus potentially explored as therapeutic agent in oral candidiasis. Purpose: The aim of this study was to examine the antifungal property Sticophus hermanii and Holothuria atra extract against Candida albicans and its cytotoxicity to human gingiva-derived mesenchymal stem cell. Methods: The study was an experimental laboratories research with post test only control group design. Methanolic extract of Sticophus hermanii and Holothuria atra in concentrations of 1%, 0.5%; 0.25%; 0.13%, 0.07%; 0.03%, 0.02% and 0.01%; were tested its cytotoxicity on gingiva-derived mesenchymal stem cell. Cell viability were measured by MTT assay. The antifungal property against Candida albicans was tested by disk diffusion method. Data were analyzed by ANOVA followed by LSD. Results: Extract of Sticophus hermanii showed no cytotoxicity in all concentrations (p>0.05), while Holothuria atra showed toxicity in the concentration of 1% and not cytotoxic in the concentrations below (p<0.05). Both sea cucumber extract could inhibit the growth Candida albicans, in vitro, proved by the clear zone around the disc in all concentrations (p<0.05). Conclusion: Stichopus hermanii and Holothuria atra extract had the antifungal effect against Candida albicans. Sea cucumber extract were not cytotoxic togingiva-derived mesenchymal stem cell in the concentration of Sticophus hermanii ≤ 1% and Holothuria atra ≤ 0.5%.Latar belakang: Teripang telah diketahui mempunyai berbagai khasiat medis. Sticophus hermanii dan Holothuria atra adalah spesies teripang yang telah diketahui mempunyai sifat anti jamur sehingga santat potensial untuk diekplorasi sebagai agen terapeutik pada infeksi di rongga mulut. Tujuan: Tujuan dari penelitian ini adalah untuk meneliti sifat anti jamur ekstrak Sticophus hermanii and Holothuria atra terhadap Candida albicans dan sitotoksisitasnya terhadap stem sel mesenkimal yang berasal dari gingiva manusia. Metode: Penelitian ini merupakan penelitian eksperimental laboratoris dengan rancangan post test only control group design. Ekstrak metanol Sticophus hermanii dan Holothuria atra pada konsentrasi 1%, 0,5%; 0,25%; 0,13%, 0,07%; 0,03%, 0,02% and 0,01% diuji sitoksisitasnya terhadap stem sel mesenkimal yang berasal dari gingiva. Viabilitas sel diukur dengan menggunakan metode MTT. Sifat anti jamur terhadap Candida albicans diuji dengan metode difusi. Data dianalisis dengan ANOVA dan LSD. Hasil: Ekstrak Sticophus hermanii tidak menunjukkan adanya toksisitas pada seluruh konsentrasi (p>0,05), sedangkan Holothuria atra menunjukkan adanya toksisitas pada konsentrasi 1% dan tidak toksik pada konsentrasi di bawahnya (p<0,05). Kedua ekstrak mampu menghambat pertumbuhan Candida albicans in vitro yang ditunjukkan dengan adanya zona jernih disekitar disk pada semua konsentrasi (p<0,05). Simpulan: Ekstrak Stichopus hermanii dan Holothuria atra mempunyai daya anti jamur terhadap Candida albicans. Ekstrak teripang bersifat tidak toksik terhadap stem sel mesenkimal yang berasal dari gingiva masing-masing pada konsentrasi Sticophus hermanii ≤ 1%, dan Holothuria atra ≤ 0,5%.